2017
DOI: 10.4049/jimmunol.1700316
|View full text |Cite
|
Sign up to set email alerts
|

The Neonatal Fc Receptor and Complement Fixation Facilitate Prophylactic Vaccine-Mediated Humoral Protection against Viral Infection in the Ocular Mucosa

Abstract: The capacity of licensed vaccines to protect the ocular surface against infection is limited. Common ocular pathogens such as herpes simplex virus type 1 (HSV-1) are increasingly recognized as major contributors to visual morbidity worldwide. Humoral immunity is an essential correlate of protection against HSV-1 pathogenesis and ocular pathology, yet the ability of antibody to protect against HSV-1 is deemed limited due to the slow IgG diffusion rate in the healthy cornea. We show that a live-attenuated HSV-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 82 publications
1
30
0
Order By: Relevance
“…In this study, SD‐OCT provided a higher sensitivity for detecting clinical corneal pathology compared to histological analysis, with corneal oedema visible at six hours post‐infection using SD‐OCT, but only after 12 hours post‐infection in histology sections . In a mouse model of HSV‐1 keratitis, SD‐OCT demonstrated corneal oedema and prominent hyper‐intensities, reflective of leukocytic infiltrates, at 24 hours post‐infection . Resolution of inflammation was also monitored using SD‐OCT in mice up to 30 days post‐injection with a vaccine against HSV‐1 …”
Section: As‐oct Imaging In Animalsmentioning
confidence: 86%
See 1 more Smart Citation
“…In this study, SD‐OCT provided a higher sensitivity for detecting clinical corneal pathology compared to histological analysis, with corneal oedema visible at six hours post‐infection using SD‐OCT, but only after 12 hours post‐infection in histology sections . In a mouse model of HSV‐1 keratitis, SD‐OCT demonstrated corneal oedema and prominent hyper‐intensities, reflective of leukocytic infiltrates, at 24 hours post‐infection . Resolution of inflammation was also monitored using SD‐OCT in mice up to 30 days post‐injection with a vaccine against HSV‐1 …”
Section: As‐oct Imaging In Animalsmentioning
confidence: 86%
“…In a mouse model of HSV‐1 keratitis, SD‐OCT demonstrated corneal oedema and prominent hyper‐intensities, reflective of leukocytic infiltrates, at 24 hours post‐infection . Resolution of inflammation was also monitored using SD‐OCT in mice up to 30 days post‐injection with a vaccine against HSV‐1 …”
Section: As‐oct Imaging In Animalsmentioning
confidence: 99%
“…Our work models a prophylactic vaccination in which the primary end goal is to prevent establishment of viral latency using a murine model of ocular HSV-1 challenge. Our studies show that humoral immunity is requisite for efficient control of primary ocular HSV-1 infection and reduction of latency through a novel mechanism involving the neonatal Fc receptor and complement (3,5). As stated in our original publication, "Focus on humoral immunity as a correlate of protection against HSV-1-induced ocular disease and latency has been eclipsed over the past decade by a focus on T cell responses" (3).…”
mentioning
confidence: 83%
“…We concede that there are decisive variables that still require focused attention in the field of HSV vaccine research. These include the meager antigenic breadth of single-glycoprotein-subunit vaccines (14), sex differences (15), original antigenic sin and poor efficacy of therapeutic subunit vaccines in HSV-1/2-seropositive individuals (16,17), the utility and safety of novel adjuvants (18,19), and differential immunologic mechanisms and effective correlates of protection for primary mucosal and dermal infection by HSV-1 and HSV-2 (5,20). Resolving these issues and advancing effective vaccines to clinical trials will require rigorous yet equitable scholarly review, erudite assimilation of the literature, and the honest spirit of collegiality.…”
mentioning
confidence: 99%
“… 29 , 30 We have recently shown that CD326/epithelial cell adhesion molecule (EpCAM) is an excellent cell-surface marker for identifying CECs by flow cytometry—circumventing the need for intracellular cytokeratin staining. 31 In the same study, we found that HSV-1 infection leads to an acute increase in the total number of CECs, 31 but the phenotype and physiology of these CECs originating under inflammatory conditions have not been characterized. Here, we investigate ectopic “myeloid” antigen expression on CECs as a possible outcome of EMT following ocular surface injury, allergy, and HSV-1 infection and explore the downstream immunologic consequences.…”
mentioning
confidence: 95%